Oral health status in relation to selected salivary elements among a group of gasoline stations workers - Ammar F Hamza Al-Saeed; Ahlam T Mohammed (College of Dentistry/ University of Baghdad, 2014)
Background: Gasoline constituents and its derivatives had many hazardous effects on the general health of humans. Thus, gasoline stations workers may be affected by different types of related diseases.This study was conducted to assess selected salivary elements and their relation with dental caries, oral hygiene status and periodontal diseases among gasoline stations workers in comparison with individuals have no regular exposure to gasoline. Materials and methods: The study group consists of thirty male subjects with an age range (33-39) years who worked in different gasoline stations in different areas of Baghdad city and thirty persons that matching in age and gender and not exposed to gasoline were selected as a control group. Dental caries was recorded by lesion severity through the application of D1-4 MFS index of (Manji et al). Plaque index of Silness and Loe and calculus index of Ramfjord were used for recording oral hygiene status. Periodontal diseases were evaluated by using the gingival index of Loe and Silness and periodontal pocket depth of Carranza. Stimulated salivary samples were collected and chemically analyzed to determine the concentration of salivary calcium, phosphorous, iron, copper and lead ions. Results: Caries experience (DMFS) was higher among the study group compared with the control group with significant difference (P